Première mention de Phlebotomus (Transphlebotomus) mascittii en Slovaquie - Dvorak, Vit; Hlavackova, Kristyna; Kocisova, Alica; Volf, Petr (Parasite, 2016)
A large-scale entomological survey was carried out in summer 2016 in the Czech Republic and Slovakia. It revealed, for the first time, the presence of the phlebotomine sand fly Phlebotomus (Transphlebotomus) mascittii Grassi, 1908 (Diptera: Phlebotominae) in south-western Slovakia. Species identification of a captured female was confirmed by both morphological and sequencing (COI) analyses.
Keywords: Animals; Slovakia; DNA; Phlebotomus; Slovenská republika; Female; hmyz - vektory; zvířata; respirační komplex IV; Electron Transport Complex IV; polymerázová řetězová reakce; Insect Vectors; Polymerase Chain Reaction; ženské pohlaví